2018
DOI: 10.3892/mmr.2018.9153
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of retinoblastoma‑binding protein 4 contributes to the radiosensitivity of AGS gastric cancer cells via phosphoinositide3‑kinase/protein kinase B pathway suppression

Abstract: In the present study, the effects and underlying mechanism of RbAp48 on the radiosensitivity of AGS gastric cancer cells was investigated. Cell proliferation was determined with an MTT assay. Flow cytometry was performed to evaluate the cell cycle and apoptosis. Reverse transcription-quantitative polymerase chain reaction and western blot analysis were performed to detect mRNA and protein expression, respectively, including RbAp48, phosphoinositide 3-kinase (PI3K) and protein kinase B (Akt). The results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Tumorigenesis is also suppressed following the inhibition of RBBP4 expression. Additionally, RBBP4 overexpression enhances tumor cell radiosensitivity by inhibiting the PI3K/Akt pathway ( Jin et al, 2018 ). Analysis of the TCGA database revealed that heightened expression of RBBP4 was associated with unfavorable survival outcomes in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tumorigenesis is also suppressed following the inhibition of RBBP4 expression. Additionally, RBBP4 overexpression enhances tumor cell radiosensitivity by inhibiting the PI3K/Akt pathway ( Jin et al, 2018 ). Analysis of the TCGA database revealed that heightened expression of RBBP4 was associated with unfavorable survival outcomes in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation can also increase RBBP4 expression in AGS GC cells, leading to G 2 phase arrest. Moreover, RBBP4 enhances the radiosensitivity of these cells by inhibiting the PI3K/Akt pathway ( 121 ). These results underscore the potential of RBBP4 as a promising target for future gene therapy interventions in the treatment of GC.…”
Section: Expression and Function Of Rbbp4/7 In Diseasesmentioning
confidence: 99%